2021
DOI: 10.1136/jim-2020-001538
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Estimated Plasma Volume in Patients with Chronic Systolic Heart Failure

Abstract: Assessing congestion is challenging but important to patients with chronic heart failure (CHF). However, there are limited data regarding the association between estimated plasma volume status (ePVS) determined using hemoglobin/hematocrit data and outcomes in patients with stable CHF. We prospectively analyzed 231 patients; the median follow-up period was 35.6 months. We calculated ePVS at admission using the Duarte and Strauss formula, derived from hemoglobin and hematocrit ratios and divided patients into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…Interestingly, more PV patients with a high ePVS (54/59, 91.5%) reached the target hematocrit This study suggests that higher ePVS may be independently (of "high-risk" disease status and leukocytosis) associated with an increased risk of thrombosis in PV. As mentioned before, hypervolemia due to higher plasma volume has been associated with an increased cardiovascular mortality in the general population [6][7][8] and PV patients may be no exception. Furthermore, PV patients usually have normal or slightly increased plasma volume which is a physiological mechanism to compensate for the steady increase in blood viscosity due to rising red blood cells mass.…”
Section: Estimating Plasma Volume Using the Strauss-derived Formula M...mentioning
confidence: 79%
See 2 more Smart Citations
“…Interestingly, more PV patients with a high ePVS (54/59, 91.5%) reached the target hematocrit This study suggests that higher ePVS may be independently (of "high-risk" disease status and leukocytosis) associated with an increased risk of thrombosis in PV. As mentioned before, hypervolemia due to higher plasma volume has been associated with an increased cardiovascular mortality in the general population [6][7][8] and PV patients may be no exception. Furthermore, PV patients usually have normal or slightly increased plasma volume which is a physiological mechanism to compensate for the steady increase in blood viscosity due to rising red blood cells mass.…”
Section: Estimating Plasma Volume Using the Strauss-derived Formula M...mentioning
confidence: 79%
“…Interestingly, several recent studies have shown that the increased estimated plasma volume status (ePVS) may be associated with significant cardiovascular mortality in the general population 6 and in heart failure patients. 7,8 In these studies, plasma volumes were approximated by calculating the ePVS with the formulas, which include parameters such as patient hematocrit, hemoglobin, and/or body weight. [6][7][8] These mathematical formulas are used mostly due to the fact that measuring the red blood cell mass and plasma volumes with radioactive isotopes in everyday practice is cumbersome, expensive, and unavailable in most countries.…”
Section: Estimating Plasma Volume Using the Strauss-derived Formula M...mentioning
confidence: 99%
See 1 more Smart Citation
“…Duarte-ePV, trended towards an association with early decompensated HF clinical outcomes. Lin et al [ 20 ] higher ePVS remained significantly associated with increased rate of primary outcome in chronic systolic HF (adjusted HR 1.567, 95% CI 1.267–1.936; P < 0.001). Two studies confirmed the clinical value of ePVS for predicting the prognosis of patients with fever [ 21 ], and the prognosis of patients with acute dyspnoea [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there is a growing body of evidence that the calculated ePV formulas are useful in predicting outcomes in many different patient groups. These include patients with AHF, 3,4 chronic HF, 3,5 HF with preserved ejection fraction, 3,6 patients undergoing transcatheter aortic valve replacement, 7 myocardial infarction, 8 sepsis, 9 and allcause, cardiovascular, and oncologic mortality. 10,11 Other advantages of these ePV formulas are the ability to be transitioned for outpatient use, which would be a valuable tool for following HF patients after discharge, and their low cost compared with mPV.…”
mentioning
confidence: 99%